Front Cover: Enhanced binding by dextran‐grafting to Protein A affinity chromatographic media. Issue 7 (April 2017) - Zhao, Lan; Zhu, Kai; Huang, Yongdong; Li, Qiang; Li, Xiunan; Zhang, Rongyue; Su, Zhiguo; Wang, Qibao; Ma, Guanghui
Abstract : J. Sep. Sci. 2017, 40, 1493–1499 DOI:10.1002/jssc.201601196 The cover picture shows the binding of antibody molecules to dextran‐grafted Protein A affinity chromatographic medium. On the left, a schematic diagram of dextran‐grafted Protein A affinity chromatographic medium is depicted, showing antibody molecules (yellow) binding to Protein A ligands (green) coupled site‐directed to dextran (dark blue)‐grafted agarose‐based matrix (light blue). On the top of the right, confocal laser scanning microscopy images illustrate that immunoglobulin G molecules entered in the medium completely. At the bottom of the right, an atom force microscopy image of dextran‐grafted medium is presented, showing a very rough surface to support the binding results.